2010
DOI: 10.1002/pc.20880
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical analysis of pineapple leaf/glass hybrid fiber reinforced polyester composites

Abstract: The dynamic mechanical properties of randomly oriented intimately mixed hybrid composites based on pineapple leaf fibers (PALF) and glass fibers (GF) in unsaturated polyester (PER) matrix were investigated. The PALFs have high‐specific strength and improve the mechanical properties of the PER matrix. In this study, the volume ratio of the two fibers was varied by incorporating small amounts of GF such as PALF/GF, 90/10, 80/20, 70/30, and 50/50, keeping the total fiber loading constant at 40 wt%. The dynamic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
91
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(105 citation statements)
references
References 20 publications
8
91
0
6
Order By: Relevance
“…Previous studies 18,23 for ramie/glass fiber and pineapple/glass fiber reported analogous results. These authors justified similar C values considering that, by increasing the volume fraction, agglomeration of glass fibers takes place, decreasing the effective fiber/matrix stress transfer.…”
Section: Dynamic Mechanical Characterization Of the Laminatessupporting
confidence: 68%
“…Previous studies 18,23 for ramie/glass fiber and pineapple/glass fiber reported analogous results. These authors justified similar C values considering that, by increasing the volume fraction, agglomeration of glass fibers takes place, decreasing the effective fiber/matrix stress transfer.…”
Section: Dynamic Mechanical Characterization Of the Laminatessupporting
confidence: 68%
“…Ananas (Ananas comosus), Bromeliaceae ailesine ait çok yıllık otsu bir bitki türüdür [6,17,18,20,23,26,27,29,32,34,37,[41][42][43]. Eni ve boyu 1-2 m arasında değişiklik gösteren bu bitki meyve etrafında çevrelenen yaklaşık 2,5-6 cm kalınlığında ve 90-140 cm uzunluğunda yapraklardan (20-30 adet) oluşmaktadır [26-28, 32, 41].…”
Section: Ananas Bi̇tki̇si̇ (Pineapple Plant)unclassified
“…Silindirik lif hücrelerinin uçları kavisli (yuvarlakça), hücre çeperlerindeki lignin oranı yüksektir [16,26,41]. Dar bir lümene sahip [26,41] ananas yaprağı liflerinin selüloz oranı %70-82 arasındadır [6,8,17,19,20,27,32,41,66,67].…”
Section: Ananas Yapraği Li̇fleri̇ (Pineapple Leaf Fibers)unclassified
See 2 more Smart Citations